2002
DOI: 10.1097/00000637-200210000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Versus Epineural Sleeve Neurorrhaphy Technique: Functional and Histomorphometric Analysis

Abstract: Three methods of nerve repair involving the epineural sleeve technique were compared with conventional nerve repair using the rat sciatic nerve transection model in four groups. In group 1, the sciatic nerve was repaired using the conventional epineural technique by placing four sutures. In groups 2, 3, and 4, the epineural sleeve technique was combined with two sutures, fibrin glue, and two sutures with fibrin glue, respectively. Functional recovery was evaluated using walking track analysis, limb circumferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 11 publications
1
34
0
3
Order By: Relevance
“…Although the results of our study are in agreement with those of Siemionow et al 8 and Tetik et al, 9 there are distinct differences between the two animal models: 1) Our study was performed in rabbits. In contrast, the epineural sleeve technique studies 8,9 used the rat sciatic transection model.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although the results of our study are in agreement with those of Siemionow et al 8 and Tetik et al, 9 there are distinct differences between the two animal models: 1) Our study was performed in rabbits. In contrast, the epineural sleeve technique studies 8,9 used the rat sciatic transection model.…”
Section: Discussionsupporting
confidence: 91%
“…Tetik et al 9 compared the epineural sleeve technique with conventional nerve repair using the rat sciatic nerve transection model. They suggested that the epineural sleeve technique was provided faster functional recovery and improved nerve regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Para evitar estos inconvenientes, resulta útil efectuar un contra apoyo con una pinza de microcirugía en el momento de pasar el hilo. El número de puntos de sutura por grupo fascicular debe ser limitado (Mackinnon SE, 1989;Sunderland S, 1990;Harris & Tindall, 1991;Tetik et al, 2002;Maggi et al, 2003;Dvali & Mackinnon, 2003). Si se logra un buen afrontamiento, puede bastar un solo punto, gracias a la contención adicional suministrada por los puntos interfasciculares o epineurales.…”
Section:  Sutura Perineuralunclassified
“…Using our own modification of the sleeve technique, we confirmed that the sleeve technique provides better stump coaptation, prevents axoplasmic fluid leakage, reduces the amount of foreign material at the coaptation site, and directs the fasciculi to a functioning end-organ rather than letting them escape into ectopic fibrous tissue. 4,5 The epineural sleeve can be used for delivery of nerve regeneration-promoting factors. One of these, dehydroepiandrosterone, may actually improve nerve regeneration in a rat sciatic nerve crush injury model.…”
mentioning
confidence: 99%